"Am I at risk of cyberbullying"? A narrative review and conceptual framework for research on risk of cyberbullying and cybervictimization: The risk and needs assessment approach. (July 2015) - Baldry, Anna Costanza; Farrington, David P.; Sorrentino, Anna
Abstract: Bullying and its electronic evolution, cyberbullying, are widespread problems among children and adolescents. Numerous studies have been conducted that address the prevalence, nature, and possible impact of cyberbullying and strategies to prevent it (Patchin & Hinduja, 2013 ). Some recent papers have reviewed existing instruments designed to measure cyberbullying (Berne et al., 2013; Vivolo-Kantor, Martell, Holland, & Westby, 2014), while others have reviewed risk factors (Kowalski et al., 2014). The aim of the present study is to present what is known about risk factors associated with cyberbullying and cybervictimization by using an ecological framework, addressing the importance of adopting a risk and needs assessment approach to identify early who is at risk and tailor interventions. We conducted a review of cyberbullying risk factors, as well as of assessment and measurement instruments and risk and needs assessment to identify which papers fulfilled the purpose of this study. Multiple online databases ( i.e., PsychInfo, SocIndex and PubMed) were searched to identify relevant studies. The keyword search criteria were: (bull* or cyberbull* or school viol* or juvenile delinquency) AND (risk* or threat* or assess*) AND (measure* or *method*) between 2000 and February 2015. Article titles and abstracts were reviewed, and all articles that appeared relevant were retrieved in full-text format and evaluated for inclusion in the review. In addition, articles accessed electronically were hand-searched for other relevant studies. A total of 7199 potential articles were located. Of these, only 53 were considered to be directly relevant and used for the purpose of the present work. Because of the large variability of methods, construct definitions, measures and item wording used in the different studies, a meta-analysis was not possible, therefore a narrative review approach was adopted to identify risk factors according to the ecological theoretical framework. Results regarding risk factors showed that individual as well as socio-family related factors were associated with cyberbullying and cybervictimization with some slight differences for boys and girls. The strongest risk factor that was associated with cyberbullying is school bullying. This review is of relevance because it is innovative in proposing a conceptual framework for developing a risk and needs assessment tool for cyberbullying and cybervictimization.